1997
DOI: 10.1093/ps/76.12.1770
|View full text |Cite
|
Sign up to set email alerts
|

Trait association of genetic markers in the growth hormone and the growth hormone receptor gene in a White Leghorn strain

Abstract: Alleles of the growth hormone (GH) gene and GH receptor (GHR) gene were analyzed for association with juvenile body weight (HBWT), age at first egg (AFE), the hen-day rate of egg production (HDR), egg specific gravity (SPG), and egg weight (EWT) in a strain of White Leghorns. The particular strain segregated at near equal frequencies for two GH alleles defined by differences at three restriction fragment length polymorphisms (RFLP) and for two GHR alleles defined by a single RFLP. The GH genotype was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 9 publications
1
41
2
1
Order By: Relevance
“…Owing to the likely role of the GH-IGF1 system in producing polyfollicular ovaries at the onset of lay, a possible association between GHR with the number of eggs produced in the first two months was also examined, but without success. Feng et al (1997) demonstrated a significant association with age at first egg and alleles of GHR that may be worth investigating along with other components of the GH-IGFI system. Studies seeking correlations between alleles of candidate genes and quantitative traits have frequently used single-generation comparisons (eg Feng et al, 1997(eg Feng et al, , 1998Nagaraja et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Owing to the likely role of the GH-IGF1 system in producing polyfollicular ovaries at the onset of lay, a possible association between GHR with the number of eggs produced in the first two months was also examined, but without success. Feng et al (1997) demonstrated a significant association with age at first egg and alleles of GHR that may be worth investigating along with other components of the GH-IGFI system. Studies seeking correlations between alleles of candidate genes and quantitative traits have frequently used single-generation comparisons (eg Feng et al, 1997(eg Feng et al, , 1998Nagaraja et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…In the chicken GH gene, several SNP in introns have been identified and reported to be associated with growth, egg production and disease resistance [11,13,20]. Sex-linked dwarf chickens are just due to a mutation at an exon-intron splicing site of the GHR gene [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sex-linked dwarf chickens are just due to a mutation at an exon-intron splicing site of the GHR gene [17]. Another SNP that led to the presence or absence of a poly (A) signal in intron 2 was found to influence ages at first egg and egg production from 274 to 385 days [11,12]. Two SNP in the IGF-II gene were significantly related to growth and feeding traits [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polymorphic sites were located in intron 1, intron 3, and intron 4, respectively. The authors suggested that the alleles that were located within the introns might have been selected for several reasons, such as an array of egg production traits, resistance to Marek's disease, or resistance to avian leukosis Feng et al, 1997). Nie et al (2005) used denaturing high-performance liquid chromatography to investigate 4 chicken breeds, and identified 283 SNPs from 12 genes of the somatotropic axis that differed in growth and reproductive characteristics.…”
Section: Introductionmentioning
confidence: 99%